MODEL KEPEMIMPINAN SPIRITUIL MILITER ALI KHAMENEI TERHADAP KETAHANAN IDEOLOGIS DAN PERTAHANAN MANDIRI DALAM PERSPEKTIF STRATEGI PERTAHANAN INDONESIA - Mujahidin Mujahidin; Fitriyan Rupito; Tarsisius Susilo; Gusti Bagus Oka Tapayasa; H.D. Arifin Simanjuntak (JOURNAL OF LAW AND NATION, 2025)
Ali Khamenei's leadership as Iran's Supreme Leader represents a model of military spiritual leadership that places ideology as the main pillar of national defence. Under his direction, Iran has developed ideological resilience through the consolidation of religious values, the strengthening of political legitimacy, and the development of military and paramilitary forces loyal to the principles of the Islamic revolution. This strategy goes hand in hand with an independent defence policy, particularly through a resistive economy programme and domestic defence industrialisation, which includes the development of ballistic missiles, drones, and other military technology, despite facing international sanctions and isolation. This article aims to analyse Khamenei's leadership model using a transformational, adaptive, and strategic military leadership theory approach, as well as utilising SWOT analysis tools to evaluate the strengths, weaknesses, opportunities, and risks of Iran's defence strategy. The results of the study show that ideological resilience provides strong legitimacy for independent defence policies, but also carries vulnerabilities in the form of technological isolation and prolonged economic pressure. For Indonesia, there are important lessons in building a defence doctrine that is distinctive, independent, and based on national ideological values, with adaptations in accordance with Pancasila and the democratic system. Thus, the model of military spiritual leadership can be a reference in formulating an adaptive and relevant Indonesian defence strategy towards Indonesia Emas 2045.